Twenty-first century corporate reporting : effective use of technology and the Internet - Trites, Gerald (Financial accounting, auditing, and taxation collection., 2021)
This book offers a roadmap to follow-a roadmap to start on now. Most importantly, the book lays out a strong case for integrated reporting and shows how reporting on the internet is ideally suited to the creation of integrated reports. This book is of interest to executives in charge of the reporting function for their companies, students of accounting and management, and to serious investors and others with a strong interest in corporate reporting and the direction in which it is headed.